IoT-Based Pedestrian Performance Evaluation at Tegar Beriman Street - Syaiful, Syaiful; Aswatdinata, Ashar; Lutfi, Muhamad; Chayati, Nurul; Wardhani, Asri Kusuma (ASTONJADRO, 2026)
A human-oriented urban environment prioritizes pedestrians, with scale and proportions tailored to human activities. This study aims to evaluate pedestrian performance in front of the PDAM TK, Tegar Beriman Street, Bogor Regency, through an Internet of Things (IoT)-based transportation engineering approach. Tegar Beriman Street is a primary urban corridor connecting various public facilities; therefore, the availability of safe, comfortable, and accessible pedestrian infrastructure is essential. However, preliminary observations revealed significant variations in pedestrian conditions, including inconsistent sidewalk widths, pavement materials, vegetation arrangements, and supporting amenities. This research employed direct observation, IoT-assisted monitoring, and literature review to collect both primary and secondary data. Primary data were obtained through field surveys, including pedestrian volume counts, documentation of existing conditions, geometric measurements of sidewalks, and inventory of pedestrian facilities. In addition, IoT technologies such as smart sensors, CCTV-based monitoring, and digital traffic counting systems were recommended to improve the accuracy and efficiency of pedestrian performance evaluation. Secondary data were collected from relevant transportation engineering standards and technical guidelines. The results indicate that the existing pedestrian facilities do not fully comply with established standards for pedestrian safety and accessibility. Several deficiencies were identified, including inadequate facilities for persons with disabilities, inconsistent road markings, ineffective traffic signs, and insufficient supporting amenities such as lighting systems, waiting areas, waste bins, and smart crossing facilities. Furthermore, the absence of real-time pedestrian monitoring limits the effectiveness of traffic management and pedestrian safety analysis.